2003
DOI: 10.3310/hta7280
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to assess the impact of a package comprising a patient-orientated, evidence-based self-help guidebook and patient-centred consultations on disease management and satisfaction in inflammatory bowel disease

Abstract: et al. A randomised controlled trial to assess the impact of a package comprising a patientorientated, evidence-based self-help guidebook and patient-centred consultations on disease management and satisfaction in inflammatory bowel disease. Health Technol Assess 2003;7(28). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. NHS R&D HTA Programme T he NHS R&D Health Technology Assessment (HTA) Programme was set up in 1993 to ensure that high-quality research informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 120 publications
(178 reference statements)
0
55
0
Order By: Relevance
“…It is recommended that patients or their caregivers should be leading the timing of the consultations, so that they are held at a stage when the patient has poignant points to discuss. Observations in patients with inflammatory bowel disease suggest that such a patient-driven arrangement of consultations could result in a reduction in consultation frequency and also a reduction of costly 'no shows' [33]. Objective measures of disease progression or markers of vital complications such as falls will help in delivering a more individually tailored follow-up system, without the risk of losing patients who fail to report to their physician despite clear indications to do so.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that patients or their caregivers should be leading the timing of the consultations, so that they are held at a stage when the patient has poignant points to discuss. Observations in patients with inflammatory bowel disease suggest that such a patient-driven arrangement of consultations could result in a reduction in consultation frequency and also a reduction of costly 'no shows' [33]. Objective measures of disease progression or markers of vital complications such as falls will help in delivering a more individually tailored follow-up system, without the risk of losing patients who fail to report to their physician despite clear indications to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The observed association between hypermobility and TMD signs does not have a direct implication in terms of treatment for patients with TMD because hypermobility is not a modifiable risk factor. Above and beyond the contribution to our understanding of TMD in general, the individual patient and healthcare professional both benefit from information on the causality of the patientÕs disease, even when no causal treatment is possible (38). Patients and healthcare professionals alike want to know what caused the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Although intuitively of importance, enhanced patient experience of care also matters on account of an important range of other associations reported in the research literature, including improved safety-related outcomes, 38 improved self-reported health and well-being, 39 enhanced recovery, 31 increased uptake of preventative health interventions 40,41 and reduced utilisation of health-care services including hospitalisation and emergency department visits. 42 …”
Section: Patient Experience Mattersmentioning
confidence: 99%